Definitive class I human leukocyte antigen expression in gestational placentation: HLA‐F, HLA‐E, HLA‐C, and HLA‐G in extravillous trophoblast invasion on placentation, pregnancy, and parturition. (10th February 2017) - Hackmon, Rinat; Pinnaduwage, Lakmini; Zhang, Jianhong; Lye, Stephen J.; Geraghty, Daniel E.; Dunk, Caroline E.
Abstract : Problem: The extravillous trophoblasts (EVT) express HLA‐C and HLA‐G, but HLA‐E and HLA‐F are the subject of conflicting reports. In this study, we define the HLA expression profile during active EVT placental implantation, pregnancy development, and parturition. Method of study: Immunohistochemistry, q‐PCR, and Western blot were used to investigate HLA‐C, HLA‐E, and HLA‐F placental expression across gestation from the early first trimester, late first trimester, second trimester (n=10 in each), preterm gestation (n=6) to elective term cesarean section and term vaginal deliveries (n=12, 38‐41 weeks). EVT explants and Swan71 cells were used to assess HLA‐C and HLA‐F during active EVT migration. Results: HLA‐G, HLA‐C, and HLA‐F were expressed by 1st‐trimester EVT and became intracellular and weaker as gestation progressed. HLA‐E was only expressed in 1st‐trimester placenta. HLA‐F and HLA‐C mRNA and protein expression levels showed a significant increase in the fetal villous mesenchyme across gestation. HLA‐C levels increased with labor. We detected a 100‐kDa HLA‐F band in early pregnancy suggesting dimer formation on the EVT surface. These results were confirmed in EVT outgrowths and Swan71 trophoblast which showed that HLA‐F and HLA‐G are increased on the cell surface of migrating EVT, while HLA‐C was internalized. Conclusion: Expression of HLA‐F and HLA‐G on the cell surface of actively migrating EVT supports their specific role in early EVT invasion and interactions with uterine natural killer cells. HLA‐C's limited expression to the proliferative EVT suggests a protective role in the earliest events of implantation but not in active EVT invasion. We also show for the first time that HLA‐C may be involved in parturition.